Revealing the Real Madame d’Esperance - A Historical and Psychological Investigation - Parker, Adrian; Warwood, Elisabeth (Journal of Scientific Exploration, 2016)
Madame d’Esperance was a physical medium, well-known for her materialized forms which bereaved sitters often recognized as their dead relatives. A critical evaluation is made of her acclaimed biographical account, Shadow Land, with a particular focus on her activities, first in Newcastle, England and then in Gothenburg, Sweden. In this process we had access to recently discovered archives and rare publications. A presentation is made of some of the fraudulent methods used by physical mediums and the possible psychological processes behind the remarkable experiences of the sitters attending séances.